Collective dynamics in lipid membranes containing transmembrane peptides. Issue 23 (4th May 2021) - Kelley, Elizabeth G.; Butler, Paul D.; Nagao, Michihiro
Abstract : Small amounts of transmembrane peptides can significantly alter the collective dynamics in lipid membranes even when there are no changes in the average membrane structure. Abstract : Biological membranes are composed of complex mixtures of lipids and proteins that influence each other's structure and function. The biological activities of many channel-forming peptides and proteins are known to depend on the material properties of the surrounding lipid bilayer. However, less is known about how membrane-spanning channels affect the lipid bilayer properties, and in particular, their collective fluctuation dynamics. Here we use neutron spin echo spectroscopy (NSE) to measure the collective bending and thickness fluctuation dynamics in dimyristoylphosphatidylcholine (di 14 : 0 PC, DMPC) lipid membranes containing two different antimicrobial peptides, alamethicin (Ala) and gramicidin (gD). Ala and gD are both well-studied antimicrobial peptides that form oligomeric membrane-spanning channels with different structures. At low concentrations, the peptides did not have a measurable effect on the average bilayer structure, yet significantly changed the collective membrane dynamics. Despite both peptides forming transmembrane channels, they had opposite effects on the relaxation time of the collective bending fluctuations and associated effective bending modulus, where gD addition stiffened the membrane while Ala addition softened the membrane. Meanwhile, the lowest gD concentrations enhanced the collective thickness fluctuation dynamics, while the higher gD concentrations and all studied Ala concentrations dampened these dynamics. The results highlight the synergy between lipids and proteins in determining the collective membrane dynamics and that not all peptides can be universally treated as rigid bodies when considering their effects on the lipid bilayer fluctuations.